2012
DOI: 10.1108/20470891211275902
|View full text |Cite
|
Sign up to set email alerts
|

Paramedic empathy levels: results from seven Australian universities

Abstract: PurposeThe purpose of this paper is to assess the extent of empathy in paramedic students across seven Australian universities.Design/methodology/approachA cross‐sectional study was carried out using a paper‐based questionnaire employing a convenience sample of first, second, and third year undergraduate paramedic students. Student empathy levels were measured using a standardised self‐reporting instrument: the Jefferson Scale of Physician Empathy‐Health Profession Students (JSPE‐HPS).FindingsA total of 783 st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 39 publications
2
27
2
1
Order By: Relevance
“…Other studies have also shown low empathy scores among paramedic students 36,37. As out-of-hospital emergency workers, paramedics are regularly exposed to pain and suffering in often-unpredictable situations and environments 9.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also shown low empathy scores among paramedic students 36,37. As out-of-hospital emergency workers, paramedics are regularly exposed to pain and suffering in often-unpredictable situations and environments 9.…”
Section: Discussionmentioning
confidence: 99%
“…Both paramedics and paramedic students had significantly low scores for empathy (26). However, female paramedic students were identified as being more empathetic than their male counterparts (27)(28)(29). In general, empathy levels either declined (27) or improved (28,29,30) as students progressed through their coursework programs.…”
Section: Conscientiousnessmentioning
confidence: 98%
“…However, female paramedic students were identified as being more empathetic than their male counterparts (27)(28)(29). In general, empathy levels either declined (27) or improved (28,29,30) as students progressed through their coursework programs. Paramedic students (in response to empathy for medical conditions) scored the lowest for substance abuse and the highest for intellectual disability (27).…”
Section: Conscientiousnessmentioning
confidence: 99%
“….serve as an adaptive function' providing resilience in emotionally aversive emergencies (Williams et al, 2012;p. .without becoming emotionally entangled' (Williams et al, 2012;p. In recent research, empathy, assessed using generalized and specialized measures (e.g., Bellini, Baime, & Shea, 2002;Bellini & Shea, 2005), was found to decline in medical students and residents (Hojat et al, 2004;Neumann et al, 2011).…”
Section: Exposure Empathy and Arousalmentioning
confidence: 99%
“…Firstly, specialized training in medical and emergency services involves frequent and direct exposure to emotionally salient and aversive situations (Grinberg et al, 2016). For example, emergency service professionals have been found to have reduced aspects of empathy (e.g., Neumann et al, 2011;Williams et al, 2012) and downregulation of responses to the pain of others (Decety, Yang, & Cheng, 2010). For example, emergency service professionals have been found to have reduced aspects of empathy (e.g., Neumann et al, 2011;Williams et al, 2012) and downregulation of responses to the pain of others (Decety, Yang, & Cheng, 2010).…”
mentioning
confidence: 99%